A User's Guide to a Data Base of the Diversity of Pseudomonas syringae and Its Application to Classifying Strains in This Phylogenetic Complex - Berge, Odile (Public Library of Science, 2014)
The Pseudomonas syringae complex is composed of numerous genetic lineages of strains from both agricultural and environmental habitats including habitats closely linked to the water cycle. The new insights from the discovery of this bacterial species in habitats outside of agricultural contexts per se have led to the revelation of a wide diversity of strains in this complex beyond what was known from agricultural contexts. Here, through Multi Locus Sequence Typing (MLST) of 216 strains, we identified 23 clades within 13 phylogroups among which the seven previously described P. syringae phylogroups were included. The phylogeny of the core genome of 29 strains representing nine phylogroups was similar to the phylogeny obtained with MLST thereby confirming the robustness of MLST-phylogroups. We show that phenotypic traits rarely provide a satisfactory means for classification of strains even if some combinations are highly probable in some phylogroups. We demonstrate that the citrate synthase (cts) housekeeping gene can accurately predict the phylogenetic affiliation for more than 97% of strains tested. We propose a list of cts sequences to be used as a simple tool for quickly and precisely classifying new strains. Finally, our analysis leads to predictions about the diversity of P. syringae that is yet to be discovered. We present here an expandable framework mainly based on cts genetic analysis into which more diversity can be integrated.